Mitochondrial DNA Activates the NLRP3 Inflammasome and Predisposes to Type 1 Diabetes in Murine Model - Carlos, Daniela; Costa, Frederico R. C.; Pereira, Camila A.; Rocha, Fernanda A.; Yaochite, Juliana N. U.; Oliveira, Gabriela G.; Carneiro, Fernando S.; Tostes, Rita C.; Ramos, Simone G.; Zamboni, Dario S.; Camara, Niels O. S.; Ryffel, Bernhard; et al. (Frontiers in Immunology, 2017)
Although a correlation between polymorphisms of NOD-like receptor family-pyrin domain containing 3 (NLRP3) and predisposition to type 1 diabetes (T1D) has been identified, the potential function and activation of the NLRP3 inflammasome in T1D have not been clarified. The present study shows that non-obese diabetic (NOD) mice exhibited increased NLRP3, apoptosis-associated speck-like protein (ASC), and pro-IL-1β gene expression in pancreatic lymph nodes (PLNs). Similar increases in gene expression were induced by multiple low doses of streptozotocin (STZ) in C57BL/6 mice. In addition, diabetic C57BL/6 mice also exhibited increased IL-1β protein expression in the pancreatic tissue at day 7, which remained elevated until day 15. Diabetic mice also showed increased positive caspase-1 macrophages in the PLNs, which were decreased in NLRP3-/- mice, but not in ASC-/- mice, after STZ treatment. NLRP3 and IL-1R deficient mice, but not ASC-deficient mice, showed reduced incidence of diabetes, less insulitis, lower hyperglycemia and normal insulin levels compared to wild-type (WT) diabetic mice. Notably, these mice also displayed a decrease in IL-17-producing CD4 and CD8 T cells (Th17 and Tc17) and IFN--producing CD4 and CD8 T cells (Th1 and Tc1) in the PLNs. Following STZ treatment to induce T1D, NLRP3 deficient mice also exhibited an increase in myeloid-derived suppressor cell (MDSC) and mast cell numbers in the PLNs along with a significant increase in IL-6, IL-10 and IL-4 expression in the pancreatic tissue. Interestingly, diabetic mice revealed increased circulating expression of genes related to mitochondrial DNA, such as cytochrome B and cytochrome C, but not NADH dehydrogenase subunit 6 (NADH). Mitochondrial DNA (mDNA) from diabetic mice, but not from non-diabetic mice, induced significant IL-1β production and caspase-1 activation by WT macrophages, which was reduced in NLRP3-/- macrophages. Finally, mDNA administration in vivo increased Th17/Tc17/Th1/Tc1 cells in the PLNs and precipitated T1D onset, which was abolished in NLRP3-/- mice. Overall, our results demonstrate that mDNA-mediated NLRP3 activation triggers caspase-1-dependent IL-1β production and contributes to pathogenic cellular responses during the development of STZ-induced T1D.